GAMABARAN TINGKAT PENGETAHUAN IBU MENYUSUI TENTANG TEKNIK MENYUSUI YANG BENAR DI PUSKESMAS PAKUALAMAN YOGYAKARTA - Kumorojati, Ratih; Windayani, Windayani (Media Ilmu Kesehatan, 2017)
Background: Breastfeeding Mother's (ASI) is the main meal and perfect for babies, in which breast milk contains almost all the nutrients in the composition according to the needs of the baby to grow and develop optimally (Perinasia, 2009). Results of a preliminary study in Healt Pakualaman of 10 nursing mothers found, as many as 6 having problems ie breast nipple abrasions. Objective: Knowing the level of knowledge of nursing mothers about breastfeeding technique right at the health center in Yogyakarta Pakualaman. Methods: Descriptive quantitative research methods, the implementation of the research conducted at the health center in Yogyakarta Pakualaman, in November 2015. This study used purposive sampling techniques, a number of 34 respondents who had infants aged 0-6 months and still breastfeeding exclusively. Data collection tool was a questionnaire, data analysis using univariate analysis. Results: The level of knowledge of nursing mothers about breastfeeding technique right at the health center in Yogyakarta that is knowledgeable good Pakualaman as many as 10 respondents, quite as much as 22 respondents, less by 2 respondents. Conclusions: The majority of breastfeeding mothers level of knowledge about proper breastfeeding technique at the health center that is knowledgeable enough Pakualaman Yogyakarta as many as 22 respondents, well as much as 10 respondents, and less by 2 respondents.   Keywords: Knowledge,Technical Breastfeeding Right